Earth, fire and air essays of a decade - Mayuga, Sylvia L. (Anvil Publishing House, 1992)
Shortly before the Aquino assassination, the Manila Daily Bulletin’s “four horsewomen of the Apocalypse” were fired in succession. As Philippine history took a dramatic turn, Sylvia L. Mayuga, Arlene Babst, Niñez C. Olivares, and Melinda Q. de Jesus found themselves at the forefront of a struggle for the full restoration of press freedom. Earth, Fire, and Air records the changing of the guards and the events soon after, with the passion of an activist and the sensitivity of a poet.